PENDAMPINGAN SUPERVISI AKADEMIK SEBAGAI UPAYA PENINGKATAN KUALITAS PEMBELAJARAN Al-QUR’AN METODE UMMI - Azizah, Nur; Mi'ah, Mazrikhatul (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2025)
This guidance aims to enhance the quality of Ummi method instruction through academic supervision conducted by subdistrict-level Ummi coordinators. Human resources are pivotal for the effective implementation of the learning process. However, several challenges have been identified in practice, including low levels of discipline and responsibility, teaching techniques that do not conform to Ummi methodology in both classical and individual settings—such as the lack of teaching aids—an unstructured and non?standardized progression system, inadequate time allocation according to the methodology, and some instructors lacking Ummi teaching certification. The results of the guidance indicate that academic supervision has facilitated a positive transformation in teaching quality, as evidenced by improved discipline and responsibility among staff, adherence to standard Ummi teaching methodology, a structured progression system, and tangible follow?up actions. These include monthly supervision by TPQ heads or Ummi coordinators, monthly tahsin coaching by external trainers, weekly internal microteaching simulations among teachers, and benchmarking visits to other institutions. Consequently, this guidance has significantly improved the quality of Ummi method-based Qur’anic instruction.